Efeito da uniformidade de plantio e fertilização na produtividade de um clone de Pinus taeda L. - Lagemann, Monique Pimentel (2020)
With the growing increase in demand for raw material from Pinus taeda plantations, associated with the reduction of their cultivated areas and the low productivity scenario of the sites, it is necessary to evaluate silvicultural practices that develop the forestry of the species promoting productivity and sustainability. The objective of this research is to evaluate whether the different silvicultural practices affect the growth, productivity and ecological aspects of P. taeda with 12 years. Located in Telêmaco Borba-PR, the bifactorial experiment (2x2) evaluated the factors planting uniformity and fertilization (4 treatments) following the randomized block design with three replications, totaling 12 plots with 576 m² each. The levels of the factor planting uniformity were homogeneous (Ho), with the planting of all clonal seedlings in February 2007, and heterogeneous (He), with the planting of 1/3 of the seedlings in three different periods: 0, 150 and 300 days after initial planting. The levels of the factor fertilization were with (F) and without fertilization (W), with fertilization being carried out at planting and nine years later. From 2009 to 2019, annual inventories were carried out, measuring the diameter at breast height at 1.3 m (DBH), total height (h) of the first three rows and of the eight dominant trees with the highest DBH (hdom). At age 11, 12 trees were selected for destructive sampling of aboveground biomass and half of the individuals for root sampling (Ø> 10 mm). The biomass sampling procedure was carried out following the sequence: the volume calculation method Smalian, separation of the components, weighing in the field, drying of the samples and determination of the moisture content. After grinding, the levels of N, P, K, Ca and Mg were determined. With the biomass, volume and content data, equations were generated to estimate these variables for nonsampled trees. The results were submitted to ANOVA and Tukey test (p<0.05). At the end of 12 years, survival in the He planting obtained higher tree mortality (7.11%). The highest mean DAP (20.11 cm) was in F. The F treatment promoted greater growth in h (17.16 m) and hdom (19.20 m) in relation to W. Both Ho (49.97 m² ha-¹) and F (53.77 m² ha-¹) provided the largest accumulation of basal area, with competition for basal area starting at age eight in He and F. The highest volumes and MAI were obtained in Ho (339.30 m³ ha-¹; 28.27 m³ ha-¹ year-¹) and F (371.07 m³ ha-¹; 30.92 m³ ha-¹ year -¹), with the PV50 index being higher in these treatments. Both Ho (212.31 Mg ha-¹) and F (231.89 Mg ha-¹) had the highest biomass production, however only in F there was a greater allocation in the wood (53.78%). The nutrient concentrations and coefficient of biological use (CBU) differed only in the fertilization factor. The largest stocks of nutrients and nutritional exports were obtained in the Ho and F treatments. Harvesting only the stem is the option with the least environmental impact, while the export of stem+canopy intensifies the removal of nutrients in W.